The Paradoxes of Antiquity in Modern Italy - Weststeijn, Arthur (Incontri. Rivista europea di studi italiani, 2018)
Review of: Philippe Foro (ed.), L’Italie et l’Antiquité du Siècle des lumières à la chute du fascisme, Toulouse, Presses universitaires du Midi, 2017, 303 p., ISBN: 9782810705030, € 23,00. Helen Roche & Kyriakos N. Demetriou (eds.), Brill’s Companion to the Classics, Fascist Italy and Nazi Germany, Leiden-Boston, Brill, 2018, 471 p., ISBN: 9789004299061, € 165,00.